A New Investigation into a Linear Operator Connected to Gaussian Hypergeometric Functions - Bunyan, Amani; Ghanim, F.; Al-Janaby, Hiba Fawzi (Iraqi Journal of Science, 2024)
In this work we introduce new subclasses of meromorphic functions in punctured unit disk and analyzes numerous connections and various features of these subclasses by making use of the linear operator that is connected to Gaussian hypergeometric functions.